Controle de altitude e ângulo de guinada de um mini-helicóptero - Santana, Lucas Vago (2011)
This work presents a framework for sensing and communication, designed to allow the control of a mini-helicopter in autonomous ight, from a ground computer. Such structure allows the capture and transmission of the data related to the current state of the aircraft to the ground station and the transmission of the control signals needed to command it during a mission. The text also presents a dynamic model of the aircraft and a controller is proposed to control the altitude and the yaw angle of the mini-helicopter during a ight on the vertical axis. The ltering and sensor fusion techniques used to obtain the attitude of the helicopter with the use of an inertial measurement unit are also covered. Finally, experimental results are presented, validating the controller, the sensing and communication structure and the assumptions made during the development of the work